Upaya Guru Pendidikan Agama Islam DalamP Nilai-Nilai Pendidikan Karakter di SMP Islam Terpadu Mutiara Insan Bendosari Sukoharjo Tahun Pelajaran 2014/2015 - Wahyudi, Wahyudi, Dr. Syamsul Hidayat, M.Ag, Drs. Bambang Raharjo, M.Ag (2016)
The value of character education is a very important need in education to build the next generation. Character education has the function of one of which is to develop the potential to be a good basis, good thoughts,and well behaved. Islamic Junior High School Integrated Islamic Junior High School Integrated (SMP IT) Insan pearl Sukoharjo is a school that implement thorough education Islamic character. Problems that can be raised in this study is how the efforts of teachers of islamic in the cultivation of the values of character education SMP IT Mutiara Insan Sukharjo along with supporting and inhibiting factors, and describe the efforts of teachers islamic, and identify supporting factors and obstacles in the planting of the values of character education Islamic religious education teacher is a person who educates, exemplary, Islam teaches religious knowledge and conduct counseling to the students towards physical and spiritual maturity to be perfect man. Efforts of teachers in instilling the values of character class VIII SMP IT Mutiara Insan Sukoharjo them a) a figure or role model for students, b) implementing rules and practicing moral discipline, c) conduct deliberations democracy, d) teach values that exist in the curriculum, e) the implementation of cultural cooperation, f) the workmanship foster in students, g) undertake moral reflection. Factors supporting the cultivation of the values of character education are: a) teachers have the competence and profesinal, b) the trust of parents, c) carried out activities that support the planting of character values, d) their pocketbooks charitable activities of students, e) teachers are doing a gathering to student trustee. Inhibiting factors including: a) the negative influence of the environment outside the school, b) poor school friend, c) the busyness of teachers who lack control of students, d) the student is imitating a fascinating things. Based on the results of research and data analysis can be concluded that the efforts of teachers of Islamic in class VIII SMP IT Mutiara Insan Sukoharjo managed to have the values of character education as the value of the religious right, bersosial well, fairness, honesty, self-contained, and has the power high fighting spirit. Keywords: Effort. Islamic religious education teachers. and character education.